Remarks on symmetry analysis of Lane-Emden systems of dimensions one and two - Freire, Igor Leite (Trends in Computational and Applied Mathematics, 2013)
Some recent results on Lie group analysis of the one and bi-dimensional Lane-Emden systems are revisited.